The effects of a group-based intervention through physical activities and dietary changes in young patients with severe psychiatric disorders: a pilot study - Sentissi, Othman; Zosso, Gabrielle; Cogordon, Anouck; Chillà, Chiara (Frontiers in Sports and Active Living, 2023)
Background and objectives: The present pilot study explored the effect of the 4-F (Fit, Fun, Feel and Food) group-based program on physical, clinical and biological outcomes in young patients suffering from serious psychiatric disorders. Methods: A pre-post intervention pilot study with follow-up in a naturalistic design was carried out. Outcome measures included medical (anthropometric, body composition, cardiac and blood chemical measures), psychiatric screening, and physical fitness (EUROFIT battery). Pre-post intervention effects were explored using Student’s t-test and differences among psychiatric conditions through ANCOVA. Results: 61 outpatients were included (mean age 26.9 ± 6.1 years, 60% men), 71% were overweight or obese. 24 patients completed the full program showing no significant decrease in weight and body composition. The findings of this study are suggestive of a potential positive influence of the proposed exercise programme on muscular endurance as well as coordination, a modest potential effect on in eating behaviour with a tendency of decrease in the hunger’s level, as well as a modest benefit on mental health. The ANCOVA showed no difference according to diagnosis between-group differences outcomes. Conclusion: Despite the limitations due to low statistical power, this pilot study provides valuable insights, supporting the feasibility of the program and its potential positive impact on physical wellbeing and enhanced mental health among young patients with psychiatric disorders, sedentary behavior, and unhealthy lifestyles. These encouraging results warrant further research in controlled, larger population samples to deepen our understanding of the potential effects of such interventions.